Review of Renteria Puton, 1875 (Heteroptera: Miridae) species present in Lodos Entomological Museum, Turkey (LEMT) - Baris, Cerci; Serdar, Tezcan; Inanc, Ozgen (Magnolia Press, 2020)
The species belonging to Reuteria Puton 1875 present in Lodos Entomological Museum, Turkey (LEMT) are reviewed. Up to now, only Reuteria marqueti Puton 1875 and R. winkelmanni Gunther & Strauss 2018 had been recorded from Turkey. In this study, Reuteria riegeri torosensis ssp. n., R. atalayi sp. n. and R. serratis sp. n. are described as new subspecies and species and from Turkey, respectively. Presence of R. marqueti in Turkey is discussed and considered as doubtful. Consequently, total number of Reuteria species known from Turkey rises to four. Additionally, unknown female of R. winkelmanni is described and illustrated, and an identification key for Reuteria species of Turkey is presented.
Keywords: New species; new record; identification key